Seismic Vulnerability Evaluation in Western Bandar Lampung's Quarter Formation using the ERT Technique - Rustadi, Rustadi -; Darmawan, I Gede Boy; Sinambela, Rudi Zefrianto (Journal of Earth and Marine Technology (JEMT), 2023)
Western Bandar Lampung is rapidly evolving into a sought-after residential locale and a scenic mountainous tourist spot. Notably, this region sits atop multiple fault structures, signaling potential seismic threats. This study aims to gauge the susceptibility of superficial layers by analyzing the resistivity properties of the underlying rock. Using the ERT geoelectric method across three lines, following the Wenner-Schlumberger configuration, a length of 140 m was mapped with electrodes spaced at intervals of 5 m. The subsurface materials in the examined area displayed a resistivity range between 4 and 1050 Ohm m, characterized by a blend of weathered constituents and igneous lenses. The dominant presence of extensively weathered material, especially given its thickness, highlights possible seismic dangers, including amplification, liquefaction, and potential landslides. To mitigate the repercussions of seismic hazards stemming from these fault lines, there is an imperative need for stringent adherence to construction guidelines tailored for seismically active regions.Top of Form